Problemy badawcze w badaniach zachowań i preferencji komunikacyjnych w branży wystawienniczej - Kwiatek, Piotr; Zieliński, Marek (Research Problems in Behaviour Research and Communication Preferences in Exhibition Business, 2006)
"Among many tasks which can be fulfilled during fairs the most important is multilevel communication. Lack of research in the field of the fair communication causes problems in early stages of research projects. In the article the authors present key dilemmas which arise in the area of communication preferences and behavior exhibition business."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 460-464